Funding flows for climate change research on Africa: where do they come from and where do they go?. (14th September 2022) - Overland, Indra; Fossum Sagbakken, Haakon; Isataeva, Aidai; Kolodzinskaia, Galina; Simpson, Nicholas Philip; Trisos, Christopher; Vakulchuk, Roman
ABSTRACT : Africa has only contributed a small fraction of global greenhouse gas emissions yet faces disproportionate risks from climate change. This imbalance is one of many inequities associated with climate change and raises questions concerning the origin, distribution and thematic prioritization of funding for climate-change research on Africa. This article analyses a database comprising USD 1.51 trillion of research grants from 521 organizations around the world and covering all fields of research from 1990 to 2020. At most 3.8% of global funding for climate-change research is spent on African topics – a figure incommensurate with Africa's share of the world population and vulnerability to climate change. Moreover, institutions based in Europe and North America received 78% of funding for climate research on Africa, while African institutions received only 14.5%. Research on climate mitigation received only 17% of the funding while climate impacts and adaptation each received around 40%. Except for Egypt and Nigeria, funding supported research on former British colonies more than other African countries. The findings highlight the need to prioritise research on a broader set of climate-change issues in Africa and to increase funding for Africa-based researchers in order to strengthen African ownership of research informing African responses to climate change.